Integrating smoking cessation and alcohol use treatment in homeless populations: study protocol for a randomized controlled trial. Issue 1 (December 2015) - Ojo-Fati, Olamide; John, Florence; Thomas, Janet; Joseph, Anne; Raymond, Nancy; Cooney, Ned; Pratt, Rebekah; Rogers, Charles; Everson-Rose, Susan; Luo, Xianghua; Okuyemi, Kolawole
Abstract Background Despite progress in reducing cigarette smoking in the general U.S. population, smoking rates, cancer morbidity and related heart disease remain strikingly high among the poor and underserved. Homeless individuals' cigarette smoking rate remains an alarming 70 % or greater, and this population is generally untreated with smoking cessation interventions. Furthermore, the majority of homeless smokers also abuse alcohol and other drugs, which makes quitting more difficult and magnifies the health consequences of tobacco use. Methods/Design Participants will be randomized to one of three groups, including (1) an integrated intensive smoking plus alcohol intervention using cognitive behavioral therapy (CBT), (2) intensive smoking intervention using CBT or (3) usual care (i.e., brief smoking cessation and brief alcohol counseling). All participants will receive 12-week treatment with a nicotine patch plus nicotine gum or lozenge. Counseling will include weekly individual sessions for 3 months, followed by monthly booster group sessions for 3 months. The primary smoking outcome is cotinine-verified 7-day smoking abstinence at follow-up week 52, and the primary alcohol outcome will be breathalyzer-verified 90-day alcohol abstinence at week 52. Discussion This study protocol describes the design of the first community-based controlled trial (n = 645) designed to examine the efficacy of integrating alcohol abuse treatment with smoking cessation among homeless smokers. To further address the gap in effectiveness of evidence-based smoking cessation interventions in the homeless population, we are conducting a renewed smoking cessation clinical trial called Power to Quit among smokers experiencing homelessness. Trial registration ClinicalTrials.gov Identifier:NCT01932996 . Date of registration: 20 November 2014.